Production of hydrogen based on combined torrefaction and gasification process - Nuralyaa, Ibrahim (2016)
Fossil fuels are commonly used and highly dependent in worldwide market as the main energy sources despite of any other sources but this source is non-renewable energy. Hence, biomass is becoming the best effective alternative energy source to replace the fossil fuels in the future due to its abundances and availabilities. Different types of biomass; which are torrefied and non-torrefied biomass usually have a different impact on the production of high level of hydrogen gas which is useful in generating energy. Therefore, the objective of this study is to compare the performance of torrefied and non-torrefied biomass using gasification process. Both types of biomass considered in this study include ‘meranti’ wood, ‘cengal’ wood and ‘kulim’ wood. In this work, fluidized bed is chosen as gasifier to produce the synthesis gas. The fluidized bed gasification model is developed in Aspen Plus as a simulator by considering the hydrodynamic and reaction rate kinetics simultaneously for both biomasses. For torrefied biomass, however, the process needs to undergo pretreatment process called as torrefaction in order to increase the energy level of the biomass. Based on this pretreatment, the torrefied biomass is then used as an input to this gasifier. It is expected that the torrified biomass will gives higher performance due to the higher level production of hydrogen gas compared to the non-torrefied biomass because torrified biomass undergoes torrefaction process before proceed to gasification process will have a lower moisture content and higher heating value.